Exposure Assessment, Neurobehavioral Performances and Effectiveness of Health Promotion Program Among Automotive Workers Exposed to Organic Solvent. - Ruslan, Rumaizah (2011)
This study investigates the level of exposure, neurobehavioral performances and the effectiveness of health promotion program among automotive workers exposed to organic solvents. The trend of toluene concentrations and neurobehavioral scores were determined over 4 years. The knowledge, attitude and practices towards organic solvents handling among workers were assessed and the changes were evaluated through a health promotion program. Neurobehavioral performances using the WHO Neurobehavioral Core Test Battery (NCTB) were conducted among 48 comparative cross-sectional workers in the Paint Shop Department. The personal air exposure was monitored using the SKC 575 Series Passive Sampler. Urine was collected at the end of shift work for biological monitoring. All 280 workers in the department filled up a socio-demographic knowledge, attitude and practices (KAP) questionnaire for quasi experimental study. One hundred and four of them volunteered to participate in the health promotion program and they were classified as the intervention group. The rest who had not participate were classified as the comparative group (n=176). Post-intervention assessment was carried out 2 weeks after the program, followed by a 3 months follow-up assessment. The mean personal air toluene concentrations and urinary hippuric acid concentrations in 2008 were significantly lower (p<0.001) than in 2004. The mean standard score for NCTB tests were also significantly higher in 2008 compared to 2004 with the exception of the Santa Ana Manual Dexterity Test. Respondents had poor knowledge scores on solvent hazards and poor practices (<80%). There were significant higher scores of knowledge (p<0.001) and practices (p<0.05) among the intervention group after the program had been introduced. The intervention group had significantly higher scores in knowledge than the comparative group at the post-intervention phase (p<0.001). After a 3 months follow-up, there were significantly better scores in knowledge (p<0.001) and practices (p<0.001) for the intervention group. Findings showed that practices was influenced by the section employment as reflected by the length of time they had been working in various sections of the Paint Department. The engineering and administrative controls as the preventive measures in the department were effective in lowering the organic solvents exposure as indicated by the improvement in scores in most of the test items in the NCTB. However, as shown by the Santa Ana Manual Dexterity Test, the chronic exposure to organic solvents worsens the peripheral function which was irreversible. A health promotion as a primary prevention to solvents had improved workers’ knowledge and practices but not the attitude. The working experiences and peer group interactions had contributed to their work practices. Knowledge retention was seen after 3 months follow-up and the workers maintained safe work practices. Further medical check-up and clinical diagnosis of nervous system impairment should be carried out among respondents who was detected with the lower performance in manual dexterity. Implementation of a routine health promotion program of at least 3 months interval period is recommended in promoting a healthy, safe and quality work environment. Improved evaluation on the health promotion program and the influencing factors such as work climate and culture should be focused for the development of future program. Keywords: Organic solvents, neurobehavioral performances, health promotion program, knowledge, attitude and practices, automotive workers